Subsoil acidity in sub-Saharan Africa: What relevance for the soil health investment agenda? - Silva, João Vasco; Sida, Tesfaye S.; Chamberlin, Jordan (EiA, 2024)
Soil acidity has recently reemerged as a priority topic in agricultural policy discussions in sub-Saharan Africa. However, most of the (still limited) existing data on soil acidity is focused on conditions in the top 20 cm of the soil profile. While addressing topsoil acidity is a logical starting point for most cropping systems affected by acidity-related production constraints, the potential importance of addressing subsoil acidity remains unclear. In the face of deepening seasonal weather variability associated with climate change, addressing subsoil acidity may be strategically important. In periods of water stress, staple crops such maize may develop deeper root systems to enhance water uptake capacity and thereby overcome drought related stress. Such capacities, however, may be severely curtailed by subsoil acidity which may impede root growth in the soil profile. This elevates the question from an esoteric soil science concern to a practical large-scale soil health management inquiry. However, because so little empirical work has been done to date on this topic, the strategic relevance of this adaptation pathway is not yet well understood. We outline the main conceptual issues of relevance to agricultural development, summarize the available information, and suggest priority areas for further empirical research within the region.